Generation And Characterization Of Expressed Sequence Tags Of Oil Palm (Elaeis Guineensis) Root System - Ng, Wai Har (2005)
Root system is an essential organ in plant for water and nutrient absorption, food storage and to support the plant within the soil. Construction of a cDNA library and analysis of the cDNA clones through ESTs approach have provided several advantages in acquiring data and gathering information on many aspects of plant biology at the molecular level. A cDNA library was constructed using mRNA of oil palm root tissues. A total of 4,200 cDNA clones were randomly selected from the library, and about 3,365 ESTs with insert size ranging between 500 bp and 3,000 bp were generated. Similarity searches and analysis of the ESTs against GenBank databases were carried out. Characterization and classification of the ESTs were done based on their putative functions and biological roles. Results have shown that about 16.26% of the total ESTs did not show significant homology to the databases, whereas 21.84% were encoding hypothetical proteins in the oil palm root cDNA library. The results show that most of the functions of the isolated ESTs are still unknown. There is a need to carry out further analysis and study in order to determine and identify the putative functions of these ESTs in the root growth and development. In addition, an open reading frame of NAC gene was cloned from the oil palm root. This 11 25 bp length NAC gene was found to show high similarity to the OsNAC protein (64%), GRAB1 (58%) and OsNAC 3 protein (58%). Alignment of this gene with NAC gene from other species has found that a conserved NAC domain with 156 amino acids lenght was located at the N-terminal of the oil palm amino acid from position of 86 to 240. It also carries a putative nuclear signal peptide, which corresponds to the NAC gene to function as a transcriptional factor in the nucleus. The existence of the highly basic regions of NAC domain suggests their involvement in DNA binding, as well as their interaction with the DNA. Further analysis of the oil palm root ESTs using DNA microarrays technology was carried out to examine and study the differential gene expression patterns between the roots and stem tissues of oil palm. About 2,261 ESTs were spotted onto the solid substrate slides, and hybridized to the fluorescently labeled cDNA probes. Result indicates that about 69.65% of the ESTs isolated were specifically expressed in oil palm roots, while only 4.50% were expressed in roots, young leaf as well as in stem tissues of oil palm. This suggests that different tissues or organs in an organism have shared their gene expressions among each other for their growth and development. - s u T A N A L W L ~ -n PUTRA MAUYSlA Lastly, the results obtained have shown that the analysis of cDNA clones using ESTs approach is an effective and rapid way in isolating and identifying the genes expressed in an organism. It is also expected that the data collected from this study would be useful and informative for better understanding of molecular mechanism and development pathways in oil palm.